Trends in the development of legislation in the area of food safety in Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2019)
The purpose of this article is to describe challenges associated with enhancement of government control overagroindustrial sector in order to maintain food security. The need for government control over agricultural industrystems from the fact that the State is accountable to its citizens for establishing their standard living conditions, foodand other agricultural product supplies. This article explores the concepts, objectives and enhancement techniques forgovernment control over agroindustrial sector, challenges associated with maintaining food security and the ways toaddress these challenges.Key words: Government Control, Agroindustrial Sector, Food Security, Legal Support, Government Functions.